2018
DOI: 10.1016/j.brainres.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Combined hypoxia and hypercapnia, but not hypoxia alone, suppresses neurotransmission from orexin to hypothalamic paraventricular spinally-projecting neurons in weanling rats

Abstract: Both orexin neurons in the lateral hypothalamus and spinally-projecting pre-sympathetic neurons (PSNs) in the paraventricular nucleus of the hypothalamus (PVN) play an important role in the regulation of cardiovascular function under normal conditions and during cardiovascular challenges such as hypoxia and/or hypercapnia. We have previously established, using selective optogenetic excitation of orexin neurons and pathways, there is a heterogeneous neurotransmission from orexin neurons to PSNs in the PVN. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In a hypoxia model in cultured rat hippocampal neurons, orexin-A increased intermittent hypoxemia-induced hippocampal neuronal damage by overphosphorylation of extracellular signal-regulated kinase 1/2 through the orexin receptor–phospholipase C-β1 (PLCβ1) pathway [ 43 ]. In addition, chronic exposure to hypoxia/hypercapnia has been shown to compromise neurotransmission from orexin neurons to parasympathetic cardiac vagal neurons [ 37 , 44 , 45 ]. Results from these rat studies suggest that exaggerated inhibitory neurotransmission from the lateral paragigantocellular nucleus to cardiac vagal neurons may lead to a sleep-associated high risk of tachycardia, arrhythmia, and sudden cardiac death in people with OSA [ 44 ].…”
Section: Pathophysiologic Mechanisms Of Eds Due To Osamentioning
confidence: 99%
“…In a hypoxia model in cultured rat hippocampal neurons, orexin-A increased intermittent hypoxemia-induced hippocampal neuronal damage by overphosphorylation of extracellular signal-regulated kinase 1/2 through the orexin receptor–phospholipase C-β1 (PLCβ1) pathway [ 43 ]. In addition, chronic exposure to hypoxia/hypercapnia has been shown to compromise neurotransmission from orexin neurons to parasympathetic cardiac vagal neurons [ 37 , 44 , 45 ]. Results from these rat studies suggest that exaggerated inhibitory neurotransmission from the lateral paragigantocellular nucleus to cardiac vagal neurons may lead to a sleep-associated high risk of tachycardia, arrhythmia, and sudden cardiac death in people with OSA [ 44 ].…”
Section: Pathophysiologic Mechanisms Of Eds Due To Osamentioning
confidence: 99%
“…2014; Dergacheva et al . 2016; Dergacheva & Mendelowitz, 2018) or without (Kline et al . 2007; Kc et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the hypoxiastimulated C1 cell group could activate orexin neurons (Kim et al, 2016). In contrast, hypoxia alone (weakly) or combined hypoxia and hypercapnia (more strongly) have been reported to inhibit orexin neurons in rat hypothalamic slice preparations (Dergacheva and Mendelowitz, 2017).…”
Section: Sympathetic Cardiovascular and Respiratory Regulation By Ore...mentioning
confidence: 99%